Article RETRACTED: include references that are unrelated to the subject of the article and/or the context in which they are cited Respuestas Fisiológicas de los Atletas de Baloncesto en silla de Ruedas al Programa Combinado de Entrenamiento Aeróbico y Anaeróbico (Physiological Responses of Wheelchair Basketball Athletes to a Combined Aerobic and Anaerobic Training Program): Article RETRACTED: include references that are unrelated to the subject of the article and/or the context in which they are cited - Latino, Francesca; Martinez-Roig, Rosabel; Setyawan, Hendra; Susanto, Nugroho; Anam, Khoiril; Saraiello, Emma; Tafuri, Francesco (Retos, 2024)
Entre los diversos deportes adaptados, el baloncesto en silla de ruedas se destaca como una actividad grupal muy favorecida entre las personas con paraplejia, incluidas las personas con lesión medular (LME). Los atletas que se enfrentan a esta discapacidad en particular exhiben alteraciones distintivas en sus sistemas metabólico, cardiorrespiratorio, neuromuscular y termorregulador, lo que en última instancia conduce a una disminución de la capacidad fisiológica respiratoria en comparación con las personas sanas o aquellas con diferentes formas de discapacidades. En consecuencia, el objetivo principal del presente esfuerzo de investigación es explorar el impacto de un régimen de ejercicio integral que abarque componentes aeróbicos y anaeróbicos en la mejora de la capacidad aeróbica de los atletas de baloncesto en silla de ruedas. Un total de 32 jugadores de baloncesto en silla de ruedas, con edades comprendidas entre los 34 y los 42 años, se inscribieron en el estudio, y la mitad se asignó a un grupo experimental que realizaba un entrenamiento aeróbico y anaeróbico combinado [GE, n = 16], mientras que los participantes restantes fueron asignados a un grupo de control que realizaba únicamente entrenamiento con ejercicios aeróbicos [GC, n = 16]. La distancia de propulsión de la silla de ruedas de 12 minutos se utilizó para evaluar el V̇O2máx en individuos con paraplejia, tanto antes como después de la intervención. Los resultados revelaron una interacción significativa Tiempo x Grupo para la variable distancia de propulsión en silla de ruedas de 12 minutos, destacando una mejora notable en el grupo de tratamiento (p < 0,001). Por el contrario, no se detectaron cambios sustanciales en el grupo control. Por lo tanto, los resultados sugieren que la integración de ejercicios aeróbicos y anaeróbicos produce un impacto positivo considerable en el rendimiento aeróbico de los jugadores de baloncesto en silla de ruedas. Palabras clave: fisiología; ejercicio; deporte; lesiones medulares; aptitud cardiorrespiratoria. Abstract. Among the multifarious adapted sports, wheelchair basketball stands out as a highly recommended group activity among individuals with paraplegia, including those with Spinal Cord Injury (SCI). Athletes facing this particular impairment exhibit distinct alterations in their metabolic, cardiorespiratory, neuromuscular, and thermoregulatory systems, ultimately leading to a diminished physiological respiratory capacity in comparison to able-bodied individuals or those with other forms of impairments. The primary objective of the present research endeavor is therefore to explore the impact of a comprehensive exercise regime, encompassing both aerobic and anaerobic components, upon the enhancement of the aerobic capacity of wheelchair basketball athletes. A total of 32 wheelchair basketball players, ranging in age from 34 to 42, were enlisted in the study, with half allocated to an experimental group engaging in combined aerobic and anaerobic training [EG, n = 16], while the remaining participants were assigned to a control group undertaking solely aerobic exercise training [CG, n = 16]. The 12-minute wheelchair propulsion distance was utilized to evaluate the V̇O2peak in individuals with paraplegia, both before and after the intervention. The findings revealed a significant Time x Group interaction for the 12-minute wheelchair propulsion distance variable, highlighting a notable enhancement in the treatment group (p < 0.001). In contrast, no substantial changes were detected in the control group. Thus, the outcomes suggest that the integration of aerobic and anaerobic exercise yields a highly positive impact on the aerobic performance of wheelchair basketball players. Key words: physiology; exercise; sport; spinal cord injuries; cardiorespiratory fitness.